ADAPTASI SPEECH CODE PADA MAHASISWA PERANTAUAN MINANGKABAU DI UNIVERSITAS MALIKUSSALEH - Ramadani, Dwi Ayu; Harinawati, Harinawati; Muchlis, Muchlis; Fazil, Muhammad (Jurnal Jurnalisme, 2024)
Adaptation is a problem that needs to be solved from the study of intercultural communication, because when a person or group of people communicates with other parties of different cultures it can create problems between them. This research aims to determine the process of adapting the Acehnese language among Minangkabau Overseas Students in their living environment and campus environment and the obstacles in the process of adapting the Acehnese language among Minangkabau students at Malikussaleh University. This research is qualitative research located on the Malikussaleh University campus, North Aceh. Data collection in this research was carried out by observation, interviews and documentation. This research uses Speech Code theory with four adaptation processes. First, assimilation, students try to reduce differences by learning Acehnese through campus friends and the community where they live. The second is separation where students feel they do not fit in with the environment and withdraw from the new environment and choose to interact only with the Minang environment. The third integration is that students begin to adapt and accept the new environment. Students choose to adapt to a new environment without leaving the culture they were born with. This can be seen when Minang students have mastered the Acehnese language but they have not forgotten the Minang language. Lastly, cultural hybridity, namely the emergence of a new culture, was not found because there was no formation of a new culture among Minangkabau students. The research results showed that Minangkabau students were successful in the process of adapting to the new culture and environment, but only 5 out of 7 informants succeeded in adapting to the Acehnese language.